Artikel Review : Analisis Komparatif Bahan Tambahan dalam Peningkatan Kinerja Bioplastik Pati Jagung - Soraya Rosfika Amalia; Shafa Maulidina Harizar; Siti Maesyaroh; Selvi Rahmawati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Petrochemical-based synthetic plastics pose significant environmental concerns due to their non-biodegradable nature. Bioplastics, particularly those derived from corn starch, offer a promising alternative because of their biodegradability and renewable origin. This article presents a narrative review analyzing the effects of various additives on the characteristics of corn starch-based bioplastics, including tensile strength, water absorption, and biodegradability. The review focuses on scientific publications from 2015 to 2025. Three types of additives were examined: cellulose fibers, graphene oxide (GO), and polyvinyl alcohol (PVA). The results show that the combination of starch and PVA with glycerol yields the best overall performance, achieving the highest tensile strength (1.8 MPa), moderate water resistance 60%, and rapid biodegradation within 6–10 days. While cellulose improves mechanical properties, it tends to slow down the degradation rate. GO provides only slight enhancements in mechanical and water-resistant properties. Overall, the starch–PVA blend appears to be the most promising formulation for developing eco-friendly and applicable bioplastics in the future.